Fertility Evaluation of Cryopreserved Osmanabadi Buck Semen at Field Level by Artificial Insemination of Estrus Synchronized Does - Koli, Vishalakshi; Ravindranath, Bislere M.; Sahadev, Annayappa; Sudha, Guelal; Kalmath, Gurubasayya P.; Renukaradhya, Gudepalya J. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Reproductive technologies like estrus synchronization and artificial insemination play an important role in enhancing goats’ reproductive efficiency and productivity. The present study was carried out to evaluate the fertility of cryopreserved Osmanabadi buck (5) semen through AI on 100 multiparous synchronized does. Does were selected after thorough clinico-gynecological examination and ultrasonographic evaluation for their reproductive status. From each of the selected bucks, five cryopreserved semen straws each from four ejaculates were prepared and used for inseminating the estrus synchronized does. The does were subjected to estrus synchronization protocol using an intra-vaginal sponge impregnated with 350 mg of natural progestagen for 7 days (Avikesil-S), followed by intramuscular injection of 125 μg, Cloprostenol sodium (Estrumate) on the day of sponge withdrawal. Fixed time insemination was performed 48-55 hours following sponge removal with simultaneous administration of 4 μg Buserelin acetate (Receptal). Pregnancy was confirmed using ultrasonography at 30-35 days of insemination. The conception rate varied non-significantly from 35.00 ± 9.57 to 45.00 ± 5.77 % among five bucks, with an average of 40.00 ± 3.40 %.